SYNTHESIS OF 4-ALLYLOXY-3-METHOXYPHENYLDIPYRROMETHENE AND STUDY OF THE EFFECT OF HEMIQUINONE IN THE COLORIMETRIC ZINC CATION DETECTION SYSTEM - Akbar Ferryansyah, Mohammad
Zinc has an important role in the human body, especially in maintaining immunity and protein cofactors. Zinc deficiency (<70 ug/dL urine) can lead to ongoing infections and growth retardation whereas excess zinc levels can cause side effects such as bleeding and gastric irritation. Therefore, it is necessary to monitor zinc levels in the body. Vanillin-dipyrrin (Vn-D) has the potential to be a colorimetric Zn2+ sensor by utilizing the equilibrium between phenolic and hemiquinone species. The reaction products were characterized using NMR, but there were no signals indicating phenolic-hemiquinone equilibrium in vanillin-dipyrine. Therefore, in this study, the effect and presence of hemiquinone species in a colorimetric sensor system was investigated by adding allyl groups to prevent the formation of these species. The allylation reaction of vanillin, the synthesis of 4-alyloxy 3- methoxydipyromethane, and 4-alyloxy 3-methoxydipyromethene (Alyl-Vn-D) yielded 78%, 53%, and 55% yields, respectively. In the UV-vis Allil-Vn-D titration spectrum with Zn2+, there is no peak at 552 nm which previously appeared in the UV-vis Vn-D titration spectrum indicating that the peak originates from hemiquinone species. However, there are two interactions based on the molar ratio curve, namely the [Zn2+]/[Alil-Vn-D] ratios of 1:2 and 1:1. There was no significant color change in Allil-Vn-D after the addition of Zn2+ indicating the importance of the hemiquinone species in the colorimetric sensor system. Based on the TDDFT calculation, it was also proven that the hemiquinone species had a larger ?max than the phenolic species, namely 448.3 nm and 375.7 nm and an error of 18.8% and 16.1%, respectively, from the experimental results